Clinical profile of Wilson disease in children between 1 and 12 years of age admitted at a tertiary care center - Sanikam, Hareesh; Bheeman, Basavaraj (Indian Journal of Child Health, 2019)
Background: Wilson disease (WD) is a rare autosomal recessive disorder characterized by the accumulation of copper in the liver, brain, cornea, and kidneys. Asymptomatic nature of disease at earlier stages leads to diagnostic enigma. Objective: The objective of this study was to study the clinical, biochemical, and histological profile of WD in children between 1 and 12 years of age. Methodology: It was a hospital-based descriptive study. All children between 1 and 12 years of age who were admitted with symptoms of liver disease and neuropsychiatric symptoms were screened for WD. Low serum ceruloplasmin (